The prognosis of TP53 and EGFR co-mutation in patients with advanced lung adenocarcinoma and intracranial metastasis treated with EGFR-TKIs - Gu, Weiguo; Liu, Penghui; Tang, Jiaming; Lai, Jianfei; Wang, Siya; Zhang, Jiaming; Xu, Jinbiao; Deng, Jianxiong; Yu, Feng; Shi, Chao; Qiu, Feng (Frontiers in Oncology, 2024)
Background: TP53 mutation is a poor factor for non-small cell lung cancer (NSCLC), while the effect of TP53 on prognosis in epidermal growth factor receptor (EGFR)-mutated lung adenocarcinoma (LUAD) with brain metastasis remains elusive and needs further exploration. Methods: We retrospectively analyzed 236 patients and tested for TP53-and EGFR-mutant status in metastasis LUAD patients who had received first-line EGFR-tyrosine kinase inhibitors (TKIs) treatment. Survival rates was calculate by Kaplan-Meier method. Furthermore, univariate and multivariate Cox analyses were performed to identify the independent prognostic factors. Results: There were 114 patients with confirmed non-brain metastasis (NBM), 74 patients with preliminary diagnosis early brain metastasis (EBM), and 48 patients with late brain metastasis (LBM). TP53 and EGFR co-mutations were 35/236 patients (14.8%). The median progression-free survival (PFS) and overall survival (OS) in the EGFR mutation and TP53 wildtype group was significantly longer than EGFR and TP53 co-mutation group in all advanced LUAD or NBM. Concurrently, PFS and OS were found to be not significant in EBM and LBM patients. Subgroup analysis revealed longer median PFS and OS in TP53 wildtype group compared to the TP53 mutant group in L858R patients and not significant in EGFR Exon 19 deletion patients. In LBM patients, the time-to-brain metastasis in EGFR mutation and TP53 wildtype group was longer than EGFR and TP53 co-mutation group, and TP53 mutant status was an independent prognostic factor for brain metastasis. The TP53 wildtype group exhibited a higher objective remission rate (ORR) and disease control rate (DCR) than the TP53 mutant group in NBM, EBM, and LBM patients, irrespective of primary lung and brain metastatic lesions.Conclusions: TP53/EGFR co-mutation patients receiving first-line EGFR-TKIs treatment had poor prognoses in advanced LUAD, especially with L858R mutation. Moreover, these susceptible patients treated with EGFR-TKIs may early time developed intracranial metastasis.